Political Turmoil in a Tumultuous World
XIX, 334 p. 21 illus., 20 illus. in color.
Keywords: In the last two years, Canadian society has been marked by political and ideological turmoil. How does an increasingly divided country engage a world that is itself divided and tumultuous? Political instability has been reinforced by international uncertainty: the COVID-19 pandemic, populism, Black Lives Matter, and the chaotic final year of the Trump presidency that increased tensions between the West, China and Russia. Even with a Biden presidency, these issues will continue to influence Canada’s domestic situation and its ability to engage as an effective global actor. Contributors explore issues that cause or reflect these tensions, such as Canada’s willingness to address pressing crises through multilateralism, including the COVID-19 pandemic. Can Canada forge its own path in a turbulent world? David Carment is Professor of International Affairs at the Norman Paterson School of International Affairs, Carleton University. Richard Nimijean is a member of the School of Indigenous and Canadian Studies at Carleton University and is a Visiting Professor in the Department of English and American Studies at Masaryk University.